PENGEMBANGAN VIDEO PEMBELAJARAN: STUDI AWAL KEBUTUHAN MAHASISWA PADA MATAKULIAH BIOENTREPRENEUR DI ERA PANDEMI - Erna Wijayanti (Center of Education Journal (CEJou), 2020)
This study aims to analyze the needs of students in developing teaching materials in the Bioentrepreneur course in the pandemic era. This research includes qualitative descriptive research. Collecting data using questionnaire, interview and observation techniques. The results showed that (1) 95.8% of students used reading materials in the form of writing on the website, (2) 51.9% of students stated that the most difficult topic in the Bioentrepreneur course was Financial Management, (3) 85.2% of students needed material. teaching in the form of learning videos. The conclusion of the research is it is necessary to develop teaching materials in the form of learning videos on the topic of analyzing financial management in the Bioentrepreneur course in the pandemic era